ML-08 Safety and efficacy of consolidation cytarabine for newly-diagnosed primary central nervous system lymphoma - Sasaki, Nobuyoshi (Neurooncol Adv, 2020)
Backgrounds: While consolidation therapies which incorporate whole brain radiotherapy (WBRT) and/ or chemotherapies such as high dose (HD)- cytarabine are commonly applied following induction chemotherapies in primary central nervous system lymphoma (PCNSL), the optimal treatment for consolidation therapy has not been established. We aimed to investigate the safety and efficacy of consolidation cytarabine with a dose modification policy in PCNSL. Patients and methods: PCNSL patients initially treated by R-MPV (rituximab, methotrexate, procarbazine and vincristine) and subsequently treated either by WBRT of 24Gy followed by cytarabine (WBRT-AraC group), or cytarabine alone (AraC group) were identified. WBRT was deferred in patients 71 years old or younger who had obtained a complete response (CR) after R-MPV. Cytarabine was dose-modified according to age groups (3 g/m2 in patients 70 years old or younger, 2 g/m2 in patients aged 71–75 years, 1 g/m2 in patients aged 76–80 years). Toxicity profiles, progression-free survival (PFS), overall survival (OS) were analyzed. Results: Twenty-five patients were identified (median age: 69 [range: 34–80], median KPS:70 [range: 40–90]), including 11 patients from the WBRT-AraC group, and 14 patients from the AraC group. Median PFS was unreached in the WBRT-AraC group, and 41.8 months in the AraC group. Median OS was unreached in both groups. The overall rate of grade 3/4 hematologic toxicities was high (92%), but mostly manageable without major complications. Fourteen patients received 3 g/m2, 4 patients received 2 g/m2, 7 patients received 1 g/m2 of cytarabine, and the rate of grade 4 leukopenia/ thrombocytopenia was 64%/57%, 25%/50%, and 29%/29%, respectively. Discussion: HD-cytarabine consolidation therapy with dose modification according to age groups for PCNSL was feasible and well-tolerated in patients 80 years of age or younger. The efficacy of HD-cytarabine was undetermined and further investigation is warranted.